Comparisons of Enterococcus Species Isolated From Patients Diagnosed With COVID-19 and Their Antibacterial Susceptibility With The One-Year Period Before The Pandemic - Öner, Pınar; Öner, Fatih; Aytaç, Özlem; Şenol, Feray Ferda; Arı, Nuray; Çağlar, Hatice; Toraman, Zülal Aşçı (Yuzuncu Yil Universitesi Tip Fakultesi, 2023)
In our study, the enterococci species isolated before the pandemic (BP) and the enterococci isolated from COVID-19 patients during the pandemic period (DP) and antibiotic susceptibility results were retrospectively analyzed. In these two periods, it was aimed to investigate the effects of antibiotics preferred for treatment on susceptibility status. The isolati on and antibiotic susceptibilities of enterococci were defined by conventional methods and an automatized system (VITEK 2). The antibiotic susceptibilities have been evaluated according to EUCAST. The amount of antibiotic use in our hospital during these periods was obtained from pharmacy data. For the BP period 221 (7%) enterococ ci strains were included, and for the DP period, 146 (5.9%) enterococcus species that have been isolated only from COVID-19 patients have been included in the study. In both periods, the most frequently isolated enterococcus species is E.faecalis. In DP, the susceptibilities for ampicillin, ciprofloxacin, linezolid, high-level streptomycin (HLS), teicoplanin, and vancomycin have increased when compared to BP. High-level gentamycin (HLG) and tigecycline susceptibilities have decreased in DP when compared to BP. It was observed that the increase in antibiotic use was reflected in the susceptibility rates. In the DP period, it was observed that ampicillin, vancomycin, teicoplanin, and ciprofloxacin were consumed less for the treatment, and accordingly, there was an increase in the sensitivity of these antibiotics. It was determined that the increase in the consumption of aminoglycoside, tetracycline, and tigecycline caused to decrease in the susceptibility of gentamicin and tigecycline. It was concluded that strategies for rational antibiotic prescribing to COVID-19 patients should be considered in order to prevent the negative effects of inappropriate antibiotic use from reaching levels that cannot be compensated for after the ongoing pandemic. © 2023, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: antibacterial susceptibility; antibiotic consumption; COVID-19; Enterococci; pandemic